2013
DOI: 10.1128/jvi.03180-12
|View full text |Cite
|
Sign up to set email alerts
|

Nonconserved Tryptophan 38 of the Cell Surface Receptor for Subgroup J Avian Leukosis Virus Discriminates Sensitive from Resistant Avian Species

Abstract: Subgroup J avian leukosis virus (ALV-J) is unique among the avian sarcoma and leukosis viruses in using the multimembranespanning cell surface protein Na ؉ /H ؉ exchanger type 1 (NHE1) as a receptor. The precise localization of amino acids critical for NHE1 receptor activity is key in understanding the virus-receptor interaction and potential interference with virus entry. Because no resistant chicken lines have been described until now, we compared the NHE1 amino acid sequences from permissive and resistant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 45 publications
6
60
0
Order By: Relevance
“…Our finding that W38 is present in ECL1 of the NHE1 receptor suggested that New World quails are susceptible to ALV-J, and this was directly confirmed by infecting New World quail embryo fibroblasts with a recombinant retroviral vector of subgroup J specificity. Our results not only identified New World quails susceptible to ALV-J but also validated our bioprospective approach based on the detection of W38 in galliform species (20,21). Future surveys of galliform species might reveal new NHE1 alleles with the ability to serve as functional receptors for ALV-J.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Our finding that W38 is present in ECL1 of the NHE1 receptor suggested that New World quails are susceptible to ALV-J, and this was directly confirmed by infecting New World quail embryo fibroblasts with a recombinant retroviral vector of subgroup J specificity. Our results not only identified New World quails susceptible to ALV-J but also validated our bioprospective approach based on the detection of W38 in galliform species (20,21). Future surveys of galliform species might reveal new NHE1 alleles with the ability to serve as functional receptors for ALV-J.…”
Section: Discussionmentioning
confidence: 49%
“…NHE1 nucleotide coding sequences of the following bird species, obtained in previous studies (20,21) or this study, were used: chicken (NCBI Nucleotide database accession number DQ256198.1), turkey (DQ883630.1), mountain quail (KX823320), northern bobwhite (KX823321), California quail (KX823322), Gambel's quail (KX823323), helmeted guineafowl (KX823324), Reeves=s pheasant (KX823325), ring-necked pheasant (KX823326), gray peacockpheasant (KX823327), Malayan peacock-pheasant (KX823328), green peafowl (KX823329), Japanese quail (KX823330), gray partridge (KX823331), chukar partridge (KX823332), and common mallard (KX823333). The sequences were aligned using a codon-based MUSCLE algorithm implemented in MEGA 6 software (46) and were checked manually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we identified Tva as a K subgroup receptor while comparing the host ranges of JS11C1 virus and A subgroup ALV. This comparison might also be useful for delineation of the binding site or at least definition of the amino acid residues that are critical for receptor function, as it helped to identify W38 of chicken NHE1 as the residue discriminating species susceptible or resistant to ALV-J (17). In our screen, we found only the guinea fowl to be resistant to JS11C1, and we hope to profit from future analyses of Tva polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…The host escapes this selection force via the evolution of receptor variants that exhibit decreased or even abrogated binding to retroviral envelopes. Numerous ALV-resistant receptor alleles have been described (5,(15)(16)(17), and positive selection was demonstrated to act within the extracellular loop 1 of NHE1, the critical region for ALV-J susceptibility (18). We have also identified receptor variants that lead to decreased susceptibility to avian sarcoma and leukosis virus (ASLV) infection (19,20).…”
mentioning
confidence: 98%